Retrospective analysis of EMR database to assess the effectiveness of Saccharomyces boulardii CNCM I-745 in children with acute diarrhoea during routine clinical practice. (November 2020) - Ragavan, P.S.K.; Kaur, A.; Kumar, M.; Singhal, V.; Patel, A.M.; Khunt, A.; Shah, R.; Wazeer, S.; Rathod, R.; Mane, A.; Mehta, S.; Veligandla, K.C.
Abstract: This study aimed to assess the efficacy of Saccharomyces boulardii, a yeast probiotic, in the management of acute diarrhoeal disorders in the paediatric population in outpatient settings. It was a multicentre retrospective analysis of medical records of children who were treated for acute diarrhoea by routine treatment (oral rehydration solution and zinc) with or without S. boulardii . Overall, 160 children presenting with acute diarrhoea at seven different outpatient paediatric settings were included in the study. Children were divided into two categories based on their treatment with S. boulardii (SB group) or without S. boulardii (Non-SB group). Baseline demographic, anthropometric and clinical variables were compared between the two groups. The median duration of diarrhoea post-treatment was significantly shorter in the S. boulardii group (3 days) than in the non-SB group (4 days). A significant reduction in the frequency of stools was observed post-treatment in the S. boulardii group (1.7 versus 2.5 in the non-SB group). There was a significant weight gain in the S. boulardii group post-treatment (300 g) in comparison with the non-SB group (mean loss of 400 g). This study established the positive role of S. boulardii in the management of acute diarrhoeal diseases in children. Moreover, the S. boulardii probiotic was seen to be effective in diarrhoeal diseases in children with dehydration.